Association Between the Respiratory Microbiome and Susceptibility to Influenza Virus Infection. (28th September 2019) - Tsang, Tim K; Lee, Kyu Han; Foxman, Betsy; Balmaseda, Angel; Gresh, Lionel; Sanchez, Nery; Ojeda, Sergio; Lopez, Roger; Yang, Yang; Kuan, Guillermina; Gordon, Aubree
Abstract: Background: Previous studies suggest that the nose/throat microbiome may play an important role in shaping host immunity and modifying the risk of respiratory infection. Our aim is to quantify the association between the nose/throat microbiome and susceptibility to influenza virus infection. Methods: In this household transmission study, index cases with confirmed influenza virus infection and their household contacts were followed for 9–12 days to identify secondary influenza infections. Respiratory swabs were collected at enrollment to identify and quantify bacterial species via high-performance sequencing. Data were analyzed by an individual hazard-based transmission model that was adjusted for age, vaccination, and household size. Results: We recruited 115 index cases with influenza A(H3N2) or B infection and 436 household contacts. We estimated that a 10-fold increase in the abundance in Streptococcus spp. and Prevotella salivae was associated with 48% (95% credible interval [CrI], 9–69%) and 25% (95% CrI, 0.5–42%) lower susceptibility to influenza A(H3N2) infection, respectively. In contrast, for influenza B infection, a 10-fold increase in the abundance in Streptococcus vestibularis and Prevotella spp. was associated with 63% (95% CrI, 17–83%) lower and 83% (95% CrI, 15–210%) higher susceptibility, respectively. Conclusions: Susceptibility to influenza infection is associated with the nose/throat microbiome at the time of exposure. The effects of oligotypes on susceptibility differ between influenza A(H3N2) and B viruses. Our results suggest that microbiome may be a useful predictor of susceptibility, with the implication that microbiome could be modulated to reduce influenza infection risk, should these associations be causal. Abstract : The upper respiratory microbiome may play a role in susceptibility to influenza virus. This study examines the role of the nose/throat microbiome on influenza infection using a household influenza transmission study.